2021
DOI: 10.1186/s12951-021-00945-x
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage-targeting poly(ethylene glycol) (PEG)-formononetin (FMN) nanodrug for the treatment of osteoarthritis

Abstract: Intra-articular (IA) injection is an efficient treatment for osteoarthritis, which will minimize systemic side effects. However, the joint experiences rapid clearance of therapeutics after intra-articular injection. Delivering system modified through active targeting strategies to facilitate localization within specific joint tissues such as cartilage is hopeful to increase the therapeutic effects. In this study, we designed a nanoscaled amphiphilic and cartilage-targeting polymer-drug delivery system by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 41 publications
0
23
1
Order By: Relevance
“…The synthesis of PEG-Nar was conducted based on a previous study ( Eivazi et al, 2020 ; Xiong et al, 2021 ). Briefly, 1.0 g mPEG-COOH (Mw = 2000, Macklin, China), 0.5 g naringenin (Nar, J&K Scientific, China), 1.5 g 4-dimethylamino pyridine (DMAP, Sigma-Aldrich, United States), and 3.0 g 1-(3-dimethylaminopropyl)-3-ethyl carbodiimide hydrochloride (EDC, Sigma-Aldrich, United States) were dissolved in 1.0 ml dimethyl sulfoxide (DMSO, Macklin, China) under sonication for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of PEG-Nar was conducted based on a previous study ( Eivazi et al, 2020 ; Xiong et al, 2021 ). Briefly, 1.0 g mPEG-COOH (Mw = 2000, Macklin, China), 0.5 g naringenin (Nar, J&K Scientific, China), 1.5 g 4-dimethylamino pyridine (DMAP, Sigma-Aldrich, United States), and 3.0 g 1-(3-dimethylaminopropyl)-3-ethyl carbodiimide hydrochloride (EDC, Sigma-Aldrich, United States) were dissolved in 1.0 ml dimethyl sulfoxide (DMSO, Macklin, China) under sonication for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with FMN, PEGylation of FMN had higher drug solubility and CollBP increased drug accumulation in the joint site. A variety of inflammation-related factors decreased significantly after treatment, which also ameliorated ACLT-induced cartilage destruction, and ultimately achieved an effective OA retarding effect ( Xiong et al, 2021 ). Xue et al affixed a type II collagen-targeting peptide to a mesoporous polydopamine (MPDA) dual drug delivery system (RB@MPMW) modified with a metal organic backbone (MOF).…”
Section: Biomedical Uses Of the Bone-targeted Drug Delivery Systemmentioning
confidence: 99%
“… [ 160 ] PCFMN/collagen II-binding peptide FMN Cartilage targeting In vitro & vivo Chondrocytes; Rats The in vitro test using IL-1β stimulated chondrocytes indicated that PCFMN was biocompatible and upregulated anabolic genes while simultaneously downregulated catabolic genes of the articular cartilage; PCFMN could effectively delay the progression of osteoarthritis and showed a longer joint placement time and better anti-inflammatory effect than FMN, suggesting that the cartilage targeted nanosheets have a certain therapeutic effect on osteoarthritis. [ 163 ] XG/PSBMA/collagen II-binding peptide - Cartilage targeting; Lubrication In vitro - The nanoparticles possess antioxidation verified by DPPH assay and exhibits synergistically enhanced ROS (OH, O 2 − and H 2 O 2 ) scavenging. [ 165 ] PEG-SWCNTs - Cartilage targeting In vitro & vivo Chondrocytes; Mice PEG-SWCNTs were capable to persist in the joint cavity for a prolonged time, entered the cartilage matrix, and delivered gene inhibitors into chondrocytes of both healthy and OA mice.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“…Cartilage targeting is the most popular strategy that can be achieved by modifying the PNPs with cartilage affinity groups. 162 Collagen II-binding peptide-modified formononetin (FMN)-poly (ethylene glycol) (PEG) NPs, 163 , 164 xanthan gum-poly (sulfobetaine methacrylate) (XG-PSBMA) NPs, 165 WYRGRL (a short cartilage-targeting peptide sequence)-modified PLGA NPs, 164 , 166 polyethylene glycol (PEG) chains (PEG-SWCNTs) modified with single-walled carbon nanotube (SWCNT) NPs, 44 and quaternary ammonium cation modified PLGA NPs 167 have been developed for cartilage targeting. In some instances, cartilage targeting originates in the basic material of the PNPs.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
See 1 more Smart Citation